Surgical Management of Traumatic Retinal Detachment with Primary Vitrectomy in Adult Patients - Katarzyna Nowomiejska; Tomasz Choragiewicz; Dorota Borowicz; Agnieszka Brzozowska; Joanna Moneta-Wielgos; Ryszard Maciejewski; Anselm G. Jünemann; Robert Rejdak (Journal of Ophthalmology)
Purpose. To evaluate functional and anatomical results of pars plana vitrectomy (PPV) in the retinal detachment (RD) followed by severe eye trauma. Methods. Retrospective analysis of medical records of forty-one consecutive patients treated with 23-gauge PPV due to traumatic RD. Age, gender, timing of PPV, visual acuity, and presence of intraocular foreign body (IOFB) and proliferative vitreoretinopathy (PVR) were included in the analysis. Results. Mean age of patients was 47 years; the majority of patients were men (88%). Closed globe injury was present in 21 eyes and open globe injury in 20 eyes (IOFB in 13 eyes, penetration injury in 4 eyes, and eye rupture in 3 eyes). Mean follow-up period was 14 months; mean timing of PPV was 67 days. Twenty-seven (66%) eyes had a functional success; 32 eyes (78%) had anatomical success. As a tamponade silicone oil was used in 33 cases and SF6 gas in 8 cases. Conclusions. Severe eye injuries are potentially devastating for vision, but vitreoretinal surgery can improve anatomical and functional outcomes. Among analysed pre- and intra- and postoperative factors, absence of PVR, postoperative retinal attachment, and silicone oil as a tamponade were related to significantly improved visual acuity.